Analisis Respons Dosimetri Phantom Berbasis PMMA dengan Variasi Media Air dan Nylon Menggunakan Sumber Cs-147 Berdasarkan Standar ISO 4037 - Widya Rachma Wulan; Primasari Cahya Wardhani; Fajar Timur; Wahyu Dwi Lestari; Arie Chintya Martania (Universitas Andalas, 2026)
This study analyzes the dosimetric response of Polymethyl Methacrylate (PMMA)-based phantoms with water and nylon as alternative media for radiation dose measurement.. Cylindrical phantoms resembling human extremities were fabricated using 3D printing according to the ISO 4037 standard. Dose measurements used a Thermoluminescent Dosimeter (TLD) type Hp(10) with a Cesium-137 gamma source (662 keV) at angles of 0°, 40°, and 235°. The results show that the dose in nylon consistently produced higher dose values than water at all angles. The average dose ranged from (31,95–32,20) μGy (absorbed dose) and (31,95–32,20) μSv (equivalent dose), while the nylon medium ranged from. (33,03–33,45) μGy (absorbed dose) and (33,03–33,45) μSv The percentage difference between the two media was in the range of 2,61%–3,88%, which is close to the 5% dosimetry tolerance limit by the IAEA. This variation is influenced by the scattering characteristics of the nylon material, which increase the probability of radiation interaction, particularly Compton scattering. Additionally, standard deviation values indicate that the dose distribution in water is more homogeneous than in nylon. Nevertheless, the consistency of the dose values suggests that nylon possesses good radiological equivalence to water. Therefore, nylon has the potential to be used as an alternative material in dosimetry phantom fabrication, especially in conditions where the use of water is limited.